2017
DOI: 10.1016/j.jhin.2017.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory-syncytial-virus- and rhinovirus-related bronchiolitis in children aged <2 years in an English district general hospital

Abstract: RV is the second most common pathogen associated with bronchiolitis and is isolated all year round. This may be important in those with risk factors resulting in prolonged LOS. Further research is necessary to establish the exact role of RV in this common condition, particularly outside the traditional RSV season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Bronchiolitis is the most common reason for hospitalization of infants and young children. The respiratory syncytial virus (RSV) and rhinovirus are the two most common pathogens in acute bronchiolitis 12 , and infection with either virus increases the risk for allergic diseases. Previous research reported that azithromycin can reduce wheezing episodes during RSV-mediated bronchiolitis due to its anti-inflammatory effect 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Bronchiolitis is the most common reason for hospitalization of infants and young children. The respiratory syncytial virus (RSV) and rhinovirus are the two most common pathogens in acute bronchiolitis 12 , and infection with either virus increases the risk for allergic diseases. Previous research reported that azithromycin can reduce wheezing episodes during RSV-mediated bronchiolitis due to its anti-inflammatory effect 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Only one study has reported a longer LOS in RV bronchiolitis compared to RSV bronchiolitis: Paul and colleagues enrolled a cohort of 319 hospitalized children for acute bronchiolitis, focusing on single RV or single RSV infections (65 cases for the former, 162 cases for the latter). Analyzing the mean LOS as clinical outcome emerged a greater LOS in the RV group compared with the RSV group ( p = 0.032) [ 32 ]. More studies have observed instead a correlation between RV infection and a lower LOS when this virus is compared to other viral pathogens, especially RSV [ 17 , 19 , 26 , 36 ].…”
Section: Rhinovirus Infection and Bronchiolitis Severitymentioning
confidence: 99%
“…Seven studies (30%) revealed that a positive RV test result significantly decreased the odds of receiving antibiotics, ranging from an OR of 0.25 (95% CI: 0.07-0.92) to an OR of 0.65 (95% CI: 0.54-0.79; Fig 1). 29,[35][36][37][38]40,41 Increased odds of receiving antibiotics was found in 2 studies (9%), ranging from an OR of 3.33 (95% CI: 1.07-10.34) to an OR of 6.82 (95% CI: 1.68-27.66). 43,46 No impact on antibiotic prescription rates was reported in 11 studies (48%).…”
Section: Antibiotic Prescribingmentioning
confidence: 99%